Optimization of Dikmas Lantas by Kamsel Unit in the Framework of Suppressing Traffic Violations of Riding Motorcycles Without Wearing a Helmet at Polresta Magelang - Hoesin, Kienan (Advances in Police Science Research Journal, 2024)
The traffic situation in Magelang Regency, which is so dense with the high number of residents and users of motorized vehicles, coupled with the increasing number of traffic violations committed by the community, is the background for the Magelang Police Satlantas Kamsel Unit to make efforts to prevent traffic violations. This writing aims to describe the management of the Kamsel Unit of the Magelang Police in suppressing traffic violations. The research was conducted using a qualitative approach and data collection techniques through observation, interviews and document review. In Chapter II of the conceptual literature, the author uses SWOT theory as a knife for analyzing influencing factors, as well as the Management Function theory and Management Element theory to discuss issues, the concept of Violation, the concept of Traffic, the concept of Traffic Violations, and the concept of Dikmas Then, to analyze the formulation of the problem in Chapter I. The results of the research in this final project are the efforts of the Magelang Police Traffic Unit in preventing motorized vehicle traffic violations that have been implemented, but there are still some deficiencies, starting from planning due to the absence of school targets and lack of facilities and infrastructure, organizing due to lack of personnel, actuating due to giving materials that are not optimal and controlling because the analysis and evaluation of the results of the activities are not carried out. Based on the author’s observations, the Magelang Polresta Polresta Satlantas Kamsel Unit must carry out community education activities about traffic as a whole to the community by paying attention to the required management elements and 4 xv management functions from the beginning to the end of the implementation of Traffic Dikmas so that it can be carried out optimally so that the number of traffic violations not using a helmet can decrease in Magelang Regency.